2020
DOI: 10.1029/2019cn000117
|View full text |Cite
|
Sign up to set email alerts
|

Landslide Disparities, Flume Discoveries, and Oso Despair

Abstract: Landslide dynamics is the branch of science that seeks to understand the motion of landslides by applying Newton's laws. This memoir focusses on a 40-year effort to understand motion of highly mobile-and highly lethal-landslides such as debris avalanches and debris flows. A major component of this work entailed development and operation of the U.S. Geological Survey debris flow flume, a unique, large-scale experimental facility in Oregon. Experiments there yielded new insights that informed development of math… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It thus indicates that viscoplastic models can be used to capture creeping landslide movement under quasi-static conditions (Li et al, 2023). However, these models may not always be appropriate for landslides forming within earthen materials exhibiting negligible viscosity (Iverson, 2020). In this manuscript, the proposed hydro-mechanical coupled framework was able to describe landslide creep without incorporating earthen material viscosity.…”
Section: Discussionmentioning
confidence: 98%
“…It thus indicates that viscoplastic models can be used to capture creeping landslide movement under quasi-static conditions (Li et al, 2023). However, these models may not always be appropriate for landslides forming within earthen materials exhibiting negligible viscosity (Iverson, 2020). In this manuscript, the proposed hydro-mechanical coupled framework was able to describe landslide creep without incorporating earthen material viscosity.…”
Section: Discussionmentioning
confidence: 98%
“…This provides an advantage over most elastoplastic models which lack unique solutions in post-failure scenarios (e.g., Puzrin, 2012), thus cannot be used to quantify landslide creep movement behaviors. However, several studies have shown that the viscosity of some slow-moving landslide materials is negligible, especially under the small dynamic range of motion exhibited by slow-moving landslides (e.g., Schulz et al, 2018;Iverson, 2020). Further complicating the issue, there is often a large discrepancy (more than three orders of magnitude) between viscosity values obtained from laboratory tests and the ones gathered from case study parameter back calculations (Angeli et al, 1996;Van Asch et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Viscoplastic models are able to describe a variety of slow-moving landslide behaviors and have additional modeling benefits because they ensure stable computations of landslide creeping under quasi-static conditions (i.e., no runaway instability of the landslide mass) (Perzyna, 4 1963;Needleman, 1988). Despite earthen material viscosity can be limited, which may prevent them from accurately describing some of the mechanisms that govern the landslide behavior (Schulz et al, 2018;Iverson, 2020), they can be used to quantify the landslide creep movement accurately.…”
Section: Introductionmentioning
confidence: 99%
“…Akin to laboratory-scale flume models, the boundary conditions of field-scale flume models can be varied along a channel bed. For example, the United States Geological Survey flume model initially had a smooth, broom-finished concrete surface; this was subsequently roughened by anchoring specially fabricated concrete tiles to better model natural conditions (Iverson 2020). Compared with the distance of debris flow on the smooth bed, the distance of debris flow on the roughened bed was much greater because of the size-segregation of grains, which led to the formation of coarse-grained lateral levees and constrained the lateral spreading of debris flow (Iverson 2020).…”
Section: Field-scale Flume Modelsmentioning
confidence: 99%